1995
DOI: 10.1080/00140139508925163
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of risk factors for symptoms in the neck and shoulder area

Abstract: This study was performed in order to evaluate how individual characteristics, as well as ergonomic, organizational and psychosocial factors in the work situation are associated with early symptoms in the neck and shoulder area. Nine hundred randomly drawn subjects of the working population in a semi-rural community in Sweden were mailed a questionnaire comprising the Nordic questionnaire on musculoskeletal symptoms, questions on ergonomic, organizational and psychosocial work conditions, life style factors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
2
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 14 publications
6
29
2
3
Order By: Relevance
“…The results on gender dierences in prevalences of upper extremity complaints as reported by this study are consistent with those found by others, reporting elevated risks for women within occupations (Bergqvist et al 1995, Chiang et al 1993, Nordander et al 1999, Skov et al 1996, Zetterberg and O È fverholm 1999 as well as among the general working population (De Zwart et al 1997a, Ekberg et al 1995, Feuerstein et al 1998, Franklin et al 1991, Linton 1990, Tanaka et al 1995. These gender dierences among employees have also been observed for other types of musculoskeletal symptoms such as back complaints (Dempsey et al 1997), although less marked than for upper extremity complaints (Punnett and Herbert 1999).…”
Section: Gender Dierences In Upper Extremity Complaintssupporting
confidence: 81%
See 1 more Smart Citation
“…The results on gender dierences in prevalences of upper extremity complaints as reported by this study are consistent with those found by others, reporting elevated risks for women within occupations (Bergqvist et al 1995, Chiang et al 1993, Nordander et al 1999, Skov et al 1996, Zetterberg and O È fverholm 1999 as well as among the general working population (De Zwart et al 1997a, Ekberg et al 1995, Feuerstein et al 1998, Franklin et al 1991, Linton 1990, Tanaka et al 1995. These gender dierences among employees have also been observed for other types of musculoskeletal symptoms such as back complaints (Dempsey et al 1997), although less marked than for upper extremity complaints (Punnett and Herbert 1999).…”
Section: Gender Dierences In Upper Extremity Complaintssupporting
confidence: 81%
“…among car assembly workers (Zetterberg and O È fverholm 1999), newspaper employees , salespeople (Skov et al 1996), ®sh industry workers (Chiang et al 1993;Nordander et al 1999), and oce workers (Bergqvist et al 1995). In large-scale studies of the general working population in dierent countries, the higher risk for women of the onset of these types of complaint have also been consistently observed (De Zwart et al 1997a;Ekberg et al 1995;Feuerstein et al 1998;Franklin et al 1991;Linton 1990;Tanaka et al 1995). The explanations for these gender dierences, however, are still poorly understood.…”
Section: Introductionmentioning
confidence: 95%
“…The other sixwereexcluded because they did not meet the inclusion criteria of this review. More specifically, this was because the study dealt with low back pain [Bigos et al, 1991], not specified musculoskeletal disorders [Leino and Hänninen, 1995], combined neck/shoulder disorders [Holmström et al, 1992;Ekberg et al, 1994Ekberg et al, , 1995Ohlssonetal.,1994]ortheresponsewasbelow70% [Skovetal., 1996]. Nine of the nineteen studies dealing with work-related psychosocial factors and shoulder problems included in this study (Table IV) were also included in the review of Windt et al [2000] [Dimberg et al, 1989;Kamwendo et al, 1991;Bernard et al, 1994;Johansson and Rubenowitz, 1994;Lagerström et al, 1995;Burdorf et al, 1997;Lemasters et al, 1998].…”
Section: Identification and Inclusion Of Studiesmentioning
confidence: 99%
“…More detailed information about the type of activity, intensity, duration, and frequency of exposure is necessary to accurately estimate the magnitudes of associations and possible exposureresponse relationships. Moreover, certain psychosocial conditions are associated with increased risk of musculoskeletal disorders [Bigos and Battie, 1996;Bongers et al, 1993;Houtman et al, 1994;Ahlberg-Hulthén et al, 1995;Leino and Hänninen, 1995;Ekberg et al, 1995;Papageorgiou et al, 1997]. Therefore, physical as well as psychosocial factors should preferably be measured within the same study.…”
Section: Introductionmentioning
confidence: 98%